Integration between orthodox medicine, homeopathy and acupuncture for inpatients: Three years experience in the first hospital for Integrated Medicine in Italy - Simonetta Bernardini; Franco Cracolici; Rosaria Ferreri; Massimo Rinaldi; Roberto Pulcri (Journal of Traditional and Complementary Medicine, 2015)
The hospital in Pitigliano (Tuscany) is the first hospital in Italy to put into practice a model of Integrated Medicine. This clinical setting caters for the use of complementary medicine (homeopathy and acupuncture (針灸 zhēn jiǔ)) alongside orthodox therapies (conventional medicine). The therapeutic model implicates doctors who are experts in complementary and alternative medicine (CAM; 補充與替代醫學 bǔ chōng yǔ tì dài yī xué) and the rest of the hospital personnel working together as equals. This contribution explains the difficulties, critical aspects and potential of this innovative setting. The clinical setting for Integrated Medicine was evaluated in part through observation and in part through the analysis of approval questionnaires. The writers of the questionnaires were the orthodox medical personnel and the hospital patients. The project is still evolving today in spite of the initial partial contrariety of some doctors in the hospital and some external doctors in the area. However, it can already be considered a positive experience, as confirmed by the high approval gained from many health workers and most of the hospital patients. Moreover, the follow-up carried out through specific surgeries dedicated to CAM is extremely positive. Up to now 532 inpatients suffering from acute illnesses, relapse of a chronic illness or neurological or orthopaedic rehabilitation following strokes, brain haemorrhage, neurological illness or limb prosthesis operations have been treated. This work has tried to illustrate the innovative and positive experience for the Italian public health authorities so that it may also be useful to anyone who would like to promote similar initiatives within its public health Institution.